The Influence of Vermicomposting Technology on Solubility of Eppawala Rock Phosphate - Senarathne, S. H. S.; Udumann, S. S. (International Coconut Community Journal, 2018)
The application of Eppawala Rock Phosphate (ERP) could be an economic alternative to the use of imported phosphorus fertilizer for certain annual as well as perennial crops like coconut in acid soils. But, its low solubility limits direct application. For Vermicomposting technology, which is a biodegradation process of plant and animal waste materials through earthworms, has been tested for increasing the solubility of ERP. Fresh Gliricidia leaves, fresh cow dung and grasses were mixed 1:2:1 ratio as the basic composting mixture and ERP was mixed at the ratio of 10% and 20% to the composting materials. Forty numbers of earthworms were added to each of the plastic containers with the composting mixture, having five replicates per treatment. Addition of ERP in to mixture showed no effect on the multiplication rate of earth worms. The nutrient availability of compost was measured with time and compared with the control (T1). Each treatment had the similar amount of nitrogen in the system and that indicates the addition of rock phosphate has a minimal effect or no effect on conversion or losses of available nitrogen. Addition of ERP increased the availability of phosphorus and it was significantly higher in T4 and T3 than other treatments. Available phosphorus value was significantly increased from 4% (T5 and T6) to 9 % in T3 and T4 treatments. Total potassium content decreased in all treatments compare with control. Therefore, vermicomposting can be utilized to increase the solubility of ERP while increasing the available phosphorus in the end product.